Deiksis dalam Cerpen Sepuluh Kejadian Karya Ranang Aji SP - Permanasari, Dian; Angraini, Nani; Manik, Tamara Paulina (LPPM STKIP PGRI Bandar Lampung, 2025)
This study aims to describe the types of deixis in short stories. The types of deixis in this study include personal deixis, place deixis, and time deixis. This study uses a qualitative method with descriptive analysis. Based on the results of the study, it was found that in the short story Sepuluh Kejadian by Ranang AJI SP, deixis amounted to 16 data with first person deixis 8 data (aku, -ku, saya, kita), second person deixis 4 data (-mu, kamu), third person deixis 1 data (-nya). Then, place deixis 1 data (under the acacia tree) time deixis only amounted to 2 data (nanti). So in this short story, the most frequently found is personal deixis.